Un hombre del '87 Juan Hernández López - Todd, Roberto H. (My University, 1935)
Participación de Hernández López en la Asamblea Autonomista.
Keywords: Hernández López, Juan; Barbosa, José Celso, 1857-1921; Gómez Brioso, José, 1855-1930; Partido Liberal Puertorriqueño; Blanco Sosa, Julián E., 1830-1905; Valle Atiles, Pedro del; Malaret, Pedro; Monclova, Pedro; Carbonell, Celedonio; Porrata Doria, Luis, 1845-1925; Celis Aguileta, José de; Mejía, Francisco; Arrillaga Roqué, Juan; Baldorioty de Castro, Román, 1822-1889